REFORMING OF RUSSIAN MONOPOLY’S SERVICE COMPANY (RZhD OJSC’s terminal/storage complex as example) - V. A. Ilyin (Модернизация, инновация, развитие)
Discussed in the article is substantiation of reasonable organizational decisions to be taken in the course of reforming Russian monopolies’ service companies in order to develop the environment of competition in their specialization sphere.